Early postoperative period of vagotomy and bypass operation - Pollak Götzl, Erich W (Cirugía del Uruguay, 2020)
A study is carried out of the early post-operative of 34 patients operated upon at the Surgical Clinic "B" ( University Hospital, Montevideo), for a complicated or medically intractable duodenal ulcer. The operation consisted of non-selective vagotomy associated with pyloroplastic ( 27 cases), gastrojejunostomy ( 6 cases), and antrectomy with gastrojejunostomy ( 1 case). The series includes 2 perforated ulcers, 1 bleeding ulcer and 3 cases of postpy loric stenosis of ulcerous origin. The following conclusions were inferable: 1) Absence of operative and post-operative mortality. 2) Absence of post-vagotomy gastric retencion ( gastric atony) beyond the 5th. day. 3) Absence of failures in the pyloroplasty. 4) Absence of post-operative gastroduodenal hemorrage. 5) Subsidance of the pre-operative clinical symptomatology. 6) Occurrence of diarrhea in 35 % of cases and infectious complications ( wound suppuration, acute pne umopaty) in 38,2 % 0f cases. 7) Clinical and X-ray evidence bears out the existence of a gastroduodena! dysfuntion during the first 2-4 post-operative days, marked by insufficient gastric drainage to the duodenum, ich renders necessary gastric aspiration and support feeding by the parenteral or duodenal route. In case of preoperative suspi:cion of important gastric retencion ( large hydric ypersecretories), a temporary degravitation gastrostomy is advised.